Guilt from promise-breaking and trust in markets for expert services: Theory and experiment - Adrian Beck; Rudolf Kerschbamer; Jianying Qiu; Matthias Sutter (Institute for the Study of Labor (IZA), 2010)
We examine the influence of guilt and trust on the performance of credence goods markets. An expert can make a promise to a consumer first, whereupon the consumer can express her trust by paying an interaction price before the expert's provision and charging decisions. We argue that the expert's promise induces a commitment that triggers guilt if the promise is broken, and guilt is exacerbated by higher interaction prices. An experiment qualitatively confirms our predictions: (1) most experts make the predicted promise; (2) proper promises induce consumer-friendly behavior; and (3) higher interaction prices increase the commitment value of proper promises.
Keywords: C72; C91; D82; 330; Promises; guilt; trust; credence goods; experts; reciprocity; Vertrauensgüter; Sachverständige; Dienstleistungsqualität; Vertrauen; Konsumentenverhalten; Erwartungstheorie; Theorie; Test